Oxidação de glicerol via catalisadores híbridos com absorção de luz visível - Cunha, Charles Garcia da (2024)
The world's energy demand tends to grow exponentially in the next 30 years, obliging the development of more efficient methods to supply it. One of the alternatives to solve this problem is the use of solar energy through storage in chemical bonds, with emphasis on the H2 molecule obtained from water. However, this process is still a large-scale challenge, especially in relation to the oxidation process. In this context, the oxidation of small organic molecules can circumvent this problem, increasing the production of H2 and still providing products of commercial interest. Thus, this work aims to oxidize glycerol using photoelectrocatalysts with visible light absorption based on BiVO4 and X-C3N4/BiVO4, where "X" represents different carbon nitrides (PCN, X-PHI (Na, K, or Cs), Li-PTI, and BiVO4 was synthesized via Bi electrodeposition in FTO followed by thermal conversion at 500 ºC in the presence of vanadium acetylacetonate. The nitrides were synthesized by the method of thermal condensation of melanin in the presence of chlorides of alkali metals. To make the X-C3N4/BiVO4, the nitride of interest was deposited in the FTO via spin coating and the BiVO4 synthesis procedure was followed. The thermogravimetric analysis showed that the PCN has superior thermal stability than other nitrides in oxidizing atmosphere, the other materials showed degradation of ca 30% of the mass at 500 ºC. Although the nitrides presented different values of bandgap energy, Eg, the X-C3N4/BiVO4 heterojunctions presented values of Eg similar to pure BiVO4. XRD analysis also revealed that the BiVO4 phases were not changed by the presence of nitrides but scanning SEM measurements coupled to EDS revealed regions rich in Bi and V and others rich in C and N, suggesting the formation of heterojunctions. Photoelectrochemical assays showed that BiVO4 is active for both water oxidation and glycerol oxidation (1.0 mol L-1), but with four times increase in the presence of glycerol at 1.23 V vs RHE. Clearly, the type of nitride used to make the heterojunctions influences the activity of the material for glycerol oxidation, with the order of photocurrent at 1.23 V vs RHE being: PCN > BiVO4 > Cs-PHI/BiVO4 > K-PHI/BiVO4 > Na-PHI/BiVO4 > Li-PTI/BiVO4. SEM-EDS analysis after electrochemical tests revealed that the presence of carbon nitrides induces the segregation of vanadium oxides, contributing to a decrease in activity. That way, some heterostructures show promising performance for the oxidation of the glycerol molecule. However, besides the electronic structure able to transport electron from BiVO4, is important to look for CN with thermal stability to avoid their degradation during BiVO4 synthesis.